A Rare Case of Parotid Tuberculosis in a Pediatric Patient: A Case Report - Pawar, Aditya; Sahoo, Niranjan; Sharma, Pawan; Rathi, Nidhi (Lietuvos chirurgija, 2023)
Even in countries like India where the general dictum is to consider Tuberculosis as one of the differential diagnosis to any condition that is still under evaluation. Parotid Tuberculosis is a very rare entity. There are fewer than 200 cases reported in literature worldwide of Parotid gland Tuberculosis, a form of extrapulmonary Tuberculosis. We present an interesting case of Parotid Tuberculosis which presented as unilateral swelling in the parotid region of a four-year-old male child with an underlying abscess.